Penerapan Akuntansi Kombinasi Bisnis Sebelum dan Sesudah Adopsi IFRS pada PT Bentoel Internasional Investama Tbk - Almira Siva Devina Wijarnako; Ellisa Noviana Dera; Wahyu Marginingtyas A.P; Endang Kartini Panggiarti (International Forum of Researchers and Lecturers, 2024)
In the era of globalization, companies face intense competition alongside the implementation of PSAK 22 (revised 2010) in Indonesia, particularly in the merger between PT Bentoel Internasional Investama, Tbk. and PT BAT Indonesia, Tbk. in 2010. Utilizing the purchase method according to PSAK 22, this research applies a qualitative approach with content analysis to compare the practices of business combination accounting before and after the adoption of IFRS. The research focuses on how well PT Bentoel Internasional Investama Tbk. adheres to accounting standards, especially PSAK 22 after IFRS adoption. The adoption of PSAK 22 and IFRS enhances transparency, limits potential earnings management, and improves the quality of financial reporting. Although there is an improvement in disclosing minority rights and non-controlling ownership, these aspects still require further attention. With its positive impact, this research demonstrates that the implementation of PSAK 22 and IFRS in PT Bentoel Internasional Investama, Tbk. can enhance the company's effectiveness in facing competition. Highlighting the positive impact of implementing PSAK 22 and IFRS in PT Bentoel Internasional Investama, Tbk., the research reinforces transparency, integrity, and the quality of financial reporting related to business combinations. The company is expected to be more effective in dealing with competition by reducing opportunities for earnings management practices. Recommendations for further research include expanding the sample size and conducting comparative studies for a more comprehensive understanding.